Five Configurations for Scaling Up Social Innovation: Case Examples of Nonprofit Organizations From Canada. (September 2014) - Westley, Frances; Antadze, Nino; Riddell, Darcy J.; Robinson, Kirsten; Geobey, Sean
Why do so many social innovations fail to have a broad impact? Successful social entrepreneurs and nonprofit organizations often "scale out" innovative solutions to local problems in order to affect more communities or numbers of individuals. When faced with institutional barriers, they are motivated to "scale up" their efforts to challenge the broader institutional rules that created the problem. In doing so, they must reorient their own and their organizations' strategies, becoming institutional entrepreneurs in the process. This article proposes a contextual model of pathways for system change consisting of five different configurations of key variables and informed by qualitative interview data from selected nonprofit organizations. The authors argue that the journey from social to institutional entrepreneurship takes different configurations depending on the initial conditions of the innovative initiatives. Despite an expressed desire to engage in system change, efforts are often handicapped by the variables encountered during implementation.